Travel Storytelling Theory and Practice - Woodside, Arch; Megehee, C. (Anatolia, 2009)
Building on semiological research (i.e., the study of signs and symbols of all kinds) investigating the use of symbols in cinematic portrayals of travel behavior, this article describes a phase dynamics theory of epiphany travel behavior. Core propositions of the theory include (1) epiphany travel behavior and storytelling about such travel includes identifiable phases: prequel, awakening, journey, catharsis, and post-journey storytelling and reinterpreting; (2) world and personal blocks occur; (3) during the journey the protagonist recognizes the need for help and experiences help from key facilitators to reach desired physical locations and other goal objects; and (4) experiencing an archetypal force is an outcome of the journey. Such theory building provides a gestalt view and understanding of epiphany travel behavior.